Determination of Ultra Trace Copper in Water Samples by Differential Pulse Polarography after Solid Phase Extraction - Mahmood Payehghadr; Farzaneh Nourifard (Orbital: The Electronic Journal of Chemistry, 2017)
A high selective and sensitive anodic stripping differential pulse polarographic method for determination of ultra-trace amounts of Cu2+ ion in water samples is proposed. The method is based on the separation and preconcentration of Cu2+ on an octadecyl bonded silica (ODBS) membrane disk modified by a recently synthesized triazene ligand, ([1-(ortoacyl benzene)3-(3,4-dichlorobenzene)triazene]). Various parameters such as, pH of aqueous solution (7-8), flow rates (10 mL min-1), the amount of ligand (6.0 mg) and the type of stripping solvent (0.1M nitric acid) have optimized. The breakthrough volume was greater than 500 mL with an enrichment factor of more than 100 and 3.88µg L-1 detection limit. The capacity of the modified disks is 220µg of copper per 6mg of the ligand. The effects of various cationic interferences on the percent recovery of copper ion were studied. The method was successfully applied to the determination of copper ion in different samples.DOI: http://dx.doi.org/10.17807/orbital.v9i5.1093